Influence of blade maximum thickness on airfoil performance with varied leading edge erosion rate - Sun, Jinjing; Zhang, Shuhan; Cao, Peiyu; Qi, Linze (Frontiers in Energy Research, 2023)
In this study, the effect of different blade shapes on the aerodynamic performance of NACA series airfoils under a wide variety of working conditions at Reynolds number Re=700000 was explored. The SST k-ω turbulence model was used for the CFD method to investigate the effect of leading edge erosion on the aerodynamic performance of NACA series airfoils. The results indicated that an optimal thickness range of the blade exists considering the leading edge erosion. If the airfoil was too thin or too thick, the leading edge erosion increased, and the aerodynamic performance was significantly reduced. However, the aerodynamic performance will not decrease greatly when the thickness was moderate, even if the leading edge erosion increased. For the same airfoil, the less the leading edge erosion, the better its aerodynamic performance will be. When the erosion degree (depth) of the leading edge airfoil was small, the variation of the erosion size would significantly affect the aerodynamic performance of the airfoil. When the erosion size of the leading edge increases to a certain extent, the performance of the blade decreases greatly compared with the original cases, but the sensitivity of the erosion blade performance to the change of the leading edge erosion size decreases.